2010
DOI: 10.1073/pnas.1009231107
|View full text |Cite
|
Sign up to set email alerts
|

RNA editing changes the lesion specificity for the DNA repair enzyme NEIL1

Abstract: Editing of the pre-mRNA for the DNA repair enzyme NEIL1 causes a lysine to arginine change in the lesion recognition loop of the protein. The two forms of NEIL1 are shown here to have distinct enzymatic properties. The edited form removes thymine glycol from duplex DNA 30 times more slowly than the form encoded in the genome, whereas editing enhances repair of the guanidinohydantoin lesion by NEIL1. In addition, we show that the NEIL1 recoding site is a preferred editing site for the RNA editing adenosine deam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
194
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 146 publications
(205 citation statements)
references
References 41 publications
11
194
0
Order By: Relevance
“…Lys242 is the form of NEIL1 encoded in the genome; RNA editing of NEIL1 pre-mRNA results in the edited Arg242 form, which was the NEIL1 protein studied in the sections above. The unedited Lys242 form was reported to be active toward Tg as well; in fact, the Tg excision activity of this form is ∼30-fold faster (30). We also confirmed that the Lys242 form cleaves Tg much faster than the Arg242 form ( Table 2).…”
Section: Computational Simulations Suggest That Tautomerization Promotessupporting
confidence: 74%
See 2 more Smart Citations
“…Lys242 is the form of NEIL1 encoded in the genome; RNA editing of NEIL1 pre-mRNA results in the edited Arg242 form, which was the NEIL1 protein studied in the sections above. The unedited Lys242 form was reported to be active toward Tg as well; in fact, the Tg excision activity of this form is ∼30-fold faster (30). We also confirmed that the Lys242 form cleaves Tg much faster than the Arg242 form ( Table 2).…”
Section: Computational Simulations Suggest That Tautomerization Promotessupporting
confidence: 74%
“…Whether or not NEIL1 also promotes tautomeric shifts of these substrates for efficient recognition and catalysis remains an open question at the moment. An ∼30-to 50-fold rate difference in Tg excision is observed between NEIL1 Arg242 and Lys242; yet unlike Tg, reaction rates are comparable for the two NEIL1 variants for both Gh and Sp (30). Therefore, it appears from this biochemical evidence that amino acid residues at position 242 may have different effects on the apparent reaction rates for different NEIL1 substrates.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, mRNAs encoding the DNA repair enzyme NEIL1 can be edited at a lysine codon to produce an arginine (Li et al, 2009). This edit redirects NEIL1 from removing thymine glycol in dsDNA to the repair of guanidinohydantoin lesions (Onizuka et al, 2012;Yeo et al, 2010). It is intriguing to think that editing might influence DNA repair in a manner that is consistent with environmental insults.…”
Section: Editing Precisely Regulates Protein Functionmentioning
confidence: 99%
“…To determine whether our selected ribozyme framework could be applied to any editing site, we performed a cleavage assay against an mRNA fragment of the human DNA repair enzyme Nei endonuclease VIII-like 1 (NEIL1), which contains a K/R site that is an A-to-I editing site in the coding region ( Fig. 5A; Yeo et al 2010). Accordingly, for unedited-specific cleavage, the HHR was designed to hybridize with NEIL1 RNA in the stem I and III region, and the catalytic core and loop II sequences were used in HR-F39 (HRF39-NEIL1) (Fig.…”
Section: Resultsmentioning
confidence: 99%